E-pembelajaran pakej pembelajaran enkripsi / Zulkurnain Sarman - Zulkurnain, Sarman (2002)
The existence of computers within the last three decades has opened the evolution of technology and knowledge. Executing variants works will become efficient using computers. This industry has developed and has to comply with consumer's demands and the evolutionary world of computers. Nevertheless, the misusing of this technology has effected more tight security measures to ensure the integrity of a technology remains. Hence, with the need of knowledge towards computer security, E- Pembelajaran: Pakej Pembelajaran Enkripsi (E- P: PPE) has been proposed to train students of Faculty of Computer Science and Information Technology (FCSIT) of encryption technics. Hopefully, E- P: PPE will benefit students in increasing knowledge of encryption and become the apprentice to the development of other e-learning packages.